Investigation and treatment of constrictive pericarditis - Dayem, M. K. A. (1967)
Twenty-six patients with constrictive pericarditis have been investigated and treated—by surgical in addition to medical methods in 22, and by medical management alone in four. A tuberculous aetiology was proved in only two patients but was probable in 10 others. One patient developed constriction of the heart following a stab wound, which caused a haemopericardium, and one after organization of a pericardial cyst. In the remainder no cause was found. The clinical features and diagnostic criteria are described, with emphasis on cardiac catheterization and angiocardiography. Operative results are given: two patients died after the operation, and the results are compared with other series. All surviving patients were improved: greatly in 13 and moderately in three. Four patients had a poor result due to long-standing myocardial disorder, and so we stress the importance of early operation, with reference to illustrative cases. Conversely, the practicability of treating certain patients by medical means alone is demonstrated. The criteria for operation are discussed with reference to repeated cardiac catheterization and angiocardiography.